Study of dilute nitride based structures for infrared photodetection - Liu, Wei (2010)
Dilute nitride III-V compound semiconductor materials have attracted considerable interests in recent years owing to the unique nitrogen-driving physics that are attributed to the highly localized nature of perturbations induced by nitrogen (N) band. Most research activities were about interband transition physics and applications. However, limited research work has been done for dilute-N related intersubband transition (ISBT) physics. In this thesis work, the ISBT properties in various dilute-N quantum wells (QWs) have been investigated using modified multi-band k.p models systematically. The growth and characterization of n-type InGaAsN/GaAs QWs for 8–12 µm infrared absorption are also reported. In Addition, studies on InSb1-xNx alloys with extended infrared detection ability to the long-wavelength infrared window are presented. A theoretical method based on eight- and fourteen-band k.p Hamiltonians in combination with envelope-function Fourier expansions has been developed to study ISBTs in N-free QWs. Then the ten- and sixteen-band k.p models taking the high-lying N resonant bands into consideration were developed to study ISBTs in various dilute-N QWs. The complete momentum matrix elements are derived. The ISBT selectivities on subband order, wave vector and well width in finitely deep QWs are concluded.